Functionality and Outcome in Older Patients with Severe Aortic Stenosis (FOOPAS): an interdisciplinary study concept for a prospective trial - Vogt F (Dove Medical Press, 2018)
Ferdinand Vogt,1 Susanne Wicklein,2 Markus Gosch,2 Jürgen Jessl,3 Wolfgang Hitzl,4 Theodor Fischlein,1 Matthias Pauschinger,3 Steffen Pfeiffer,1 Dennis Eckner3 1Department of Cardiac Surgery, Paracelsus Medical University, Nuremberg, Germany; 2Department of Geriatric Medicine, Paracelsus Medical University, Nuremberg, Germany; 3Department of Cardiology, Paracelsus Medical University, Nuremberg, Germany; 4Research Office – Biostatistics, Paracelsus Medical University, Salzburg, Austria Background: Frailty is a geriatric syndrome that can influence mortality and functional recovery after treatment of severe aortic stenosis (AS). The integration of standardized geriatric assessment (GA) in clinical practice is limited by a lack of consensus on how to measure it. Objectives: This study aims to compare the incremental predictive value of different frailty scales to predict the outcomes following surgical aortic valve replacement, transcatheter aortic valve implantation, and conservative treatment of severe AS. Methods: A prospective cohort of 300 older adults with severe AS will be assembled after standard clinical examinations and a comprehensive GA, including 18 different tests and values. Primary outcome parameters are overall mortality, cardiovascular mortality, quality of life, and functionality. Secondary parameters are overall complications, cardiovascular complications, and costs. Results: Expected results will contribute to the growing body of evidence on frailty based on parameters that influence clinical and functional outcome in elderly patients independent of the method of treatment. The pre-procedural assessment is expected to be valuable in discriminating new post-procedural complications from simple exacerbations of pre-existing conditions. Therefore, a new frailty test which is simple and feasible for application in a clinical routine by most medical professionals, may help in identifying patients for whom further GA should be considered. Finally, such a frailty score could support heart teams to find the right treatment for patients suffering from AS. Conclusion: Comparison of different frailty scales has not only the goal of finding a predictive value of mortality but also to bring in a meaningful improvement for each individual patient and to avoid disability or fatal outcomes. Keywords: frailty, aortic valve, geriatric assessment, transcatheter aortic valve implantation, TAVI, aortic valve replacement, AVR